HUMIRON® IS AN EFFECTIVE BIODEGRADABLE SOURCE OF CHELATED IRON FOR PLANTS: AN IRON-59 UPTAKE STUDY - Nikolić, Miroslav (Bulletin of Natural Sciences Research, 2018)
Here we tested plants’ ability to use iron (Fe) from the water-soluble commercial product Humiron® (a complex of Fe with highly purified and solubilized humic acids extracted from leonardite) as a source of chelated Fe for both strategy 1 (e.g. cucumber) and strategy 2 (e.g. barley) plant species grown under low Fe conditions. Iron from radioactive 59Fe-labelled Humiron® can easily be acquired by strategy 1 plant species via reduction of FeIII by the inducible plasma membrane-bound reductase, similarly to the reduction of synthetic FeIII-chelates. Strategy 2 plant species can also efficiently utilize Fe from Humiron® via ligand exchange between humates and phytosiderophores (PS). Moreover, the efficacy of Humiron® is comparable to Fe complexed with water-extractable humic substances obtained form peat. Being easily biodegradable this product can be used as an effective Fe source for organic crop production.
Keywords: Barley; Chlorosis; Cucumber; Humate Complex; Iron Root-acquisition Strategies; Transport